Job accessibility and spatial equity: A city of Cape Town case study - Jacomien van der Merwe; Tom de Jong (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Addressing unemployment and income inequalities in transport and land-use policies is important, particularly in South Africa, which is currently experiencing one of the highest unemployment rates and income inequality in the world. This research investigates the horizontal (geographical distribution) and vertical (distribution between income groups) impact of job accessibility within the City of Cape Town. Two accessibility measures were estimated using unique tax administrative data together with TomTom road network and speeds data to determine job accessibility, differentiating between suburbs, industries, income groups, and different travel times. The research findings show the spatial divide between worker's residence and jobs and highlight the difference in this spatial mismatch between different income levels. The results highlight the unequal distribution of accessibility across space and between different income groups and show that the impact of congestion has a greater effect on access to job opportunities for residents of low-income locations compared with those from high-income locations. This reinforces spatial inequality. This research provides insights into where transport investments should be made to increase access to jobs and reduce inequality in accessibility, which could drive further income inequality and unemployment.
Keywords: D63; R1; R41; O1; 330; job accessibility; spatial inequality; spatial mismatch; congestion; travel time; developing country